Connected Curriculum for Higher Education (University College London, 2017)
Is it possible to bring university research and student education into a more connected, more symbiotic relationship? If so, can we develop programmes of study that enable faculty, students and 'real world' communities to connect in new ways? In this accessible book, Dilly Fung argues that it is not only possible but also potentially transformational to develop new forms of research-based education. Presenting the Connected Curriculum framework already adopted by UCL, she opens windows onto new initiatives related to, for example, research-based education, internationalisation, the global classroom, interdisciplinarity and public engagement. AConnected Curriculum for Higher Education is, however, not just about developing engaging programmes of study. Drawing on the field of philosophical hermeneutics, Fung argues how the Connected Curriculum framework can help to create spaces for critical dialogue about educational values, both within and across existing research groups, teaching departments and learning communities. Drawing on vignettes of practice from around the world, she argues that developing the synergies between research and education can empower faculty members and students from all backgrounds to contribute to the global common good.